Penyuluhan Teknik Pembukuan Sederhana Dan Aspek Permodalan PKBL Bagi UKM Cluster Tepung Tapioka, Kabupaten Bogor - Iha Haryani H; Ahmad Djamil (SULUH: Jurnal Abdimas, 2019)
Micro, small and medium enterprises (MSMEs) are one of the cornerstones of the Indonesian economy. UMKM has been recognized as very strategic and important not only for economic growth, but also for equitable distribution of income because of its very important role. Indonesia pays special attention to the development of MSMEs by facilitating and providing access to productive resources. Community Service conducted by the Faculty of Economic and Business Service Team is to conduct counseling for the Bogor Regency tapioca flour cluster SMEs, namely regarding simple bookkeeping techniques and capital aspects of the Partnership and Community Development program in collaboration with BNI bank.